Halal Reimagined: Ir4.0 Tech Drives Sustainability And Inclusivity In Islamic Monetary Economics - Adlin Masood; Umi Hamidaton Mohd Soffian Lee; Alina Abdul Rahim (Universiti Sains Islam Malaysia, 2025)
Indexed by Scopus/MyCite